International Medical Graduate Integration into the Sunshine Coast Hospital and Health Service (SCHHS): A practice note - Thi Aung (Asia Pacific Journal of Health Management)
Australia’s healthcare workforce shortage demands innovative solutions to ensure the delivery of high-quality healthcare. International Medical Graduates (IMGs), particularly those on the standard pathway—doctors whose primary medical qualifications are obtained in non-comparable healthcare systems such as those outside the UK, USA, Canada, Ireland, or New Zealand—play a crucial role in bridging workforce gaps. However, transitioning into the Australian healthcare system presents significant challenges for these IMGs, including adapting to clinical practices, communication styles, and cultural norms.